The Thames and I : a memoir by Prince Naruhito of two years at Oxford. - Naruhito, Emperor of Japan, 1960- (RENAISSANCE Books, 2019)
Prior to becoming Crown Prince of Japan in 1989, following the death of his grandfather Emperor Showa, Prince Naruhito studied at Merton College, Oxford, from June 1983 to October 1985. This memoir, which includes a colour plate section incorporating photographs taken by the Prince, explores his daily life, studies and recreational experiences.